لغات العرب في كتاب معاني القرآن للأخفش الأوسط وعلاقة ذلك بآرائه النحوية - عرباوي, أحمد الشايب (University of Eloued جامعة الوادي, 2015)
يعد كتاب " معاني القرآن " للأخفش الأوسط أهم مصدر قديم في النحو العربي بعد كتاب سيبويه ، لاشتماله على جملة من القضايا النحوية مستدلا لها بكلام العرب ، وقد أشار الأخفش في كتابه إلى العديد من لغات العرب التي تساعد على فهم النص القرآني . إن تناول الأخفش لهذه اللغات يم ّ كن من التعرف على رأيه إزاء جملة من القضايا كانت محل نقاش وجدل عبر العصور منها : التخريج النحوي ، دائرة الاحتجاج اللغوي ، طبيعة لغة القرآن The book entitled " the meanings of koran " written by Al-akhfash alawsatt ,was the most important source in the Arabic grammar after Sibawayh's book , because it includes a number of grammatical issues based on the Arabic speech . Different arabe languages has been showed by Al-akhfash in his book , these languages help to understand the koranic text . Through this presentation of these arabe languages , we can define Alakhfash's opinions about a number of issues like : graduation grammar , linguistic circle of protest , the nature of the language of the holly Koran
Keywords: النحو العربي، كتاب معاني القرآن، الأخفش الأوسط; Arabic grammar, the meanings of koran, Al-akhfash alawsatt